Mobility care in nursing homes: development and psychometric evaluation of the kinaesthetics competence self-evaluation (KCSE) scale - Heidrun Gattinger; Beate Senn; Virpi Hantikainen; Sascha Köpke; Stefan Ott; Helena Leino-Kilpi (BMC, 2017)
Abstract Background Impaired mobility is a prevalent condition among care-dependent persons living in nursing homes. Therefore, competence development of nursing staff in mobility care is important. This study aimed to develop and initially test the Kinaesthetics Competence Self-Evaluation (KCSE) scale for assessing nursing staff's competence in mobility care. Methods The KCSE scale was developed based on an analysis of the concept of nurses' competence in kinaesthetics. Kinaesthetics is a training concept that provides theory and practice about movement foundations that comprise activities of daily living. The scale contains 28 items and four subscales (attitude, dynamic state, knowledge and skills). Content validity was assessed by determining the content validity index within two expert panels. Internal consistency and construct validity were tested within a cross-sectional study in three nursing homes in the German-speaking region of Switzerland between September and November 2015. Results The content validity index for the entire scale was good (0.93). Based on a sample of nursing staff (n = 180) the internal consistency results were good for the whole scale (Cronbach's alpha = 0.91) and for the subscales knowledge and skills (α = 0.91, 0.86), acceptable for the subscale attitude (α = 0.63) and weak for the subscale dynamic state (α = 0.54). Most items showed acceptable inter-item and item-total correlations. Based on the exploratory factor analysis, four factors explaining 52% of the variance were extracted. Conclusion The newly developed KCSE scale is a promising instrument for measuring nursing staff's attitude, dynamic state, knowledge, and skills in mobility care based on kinaesthetics. Despite the need for further psychometric evaluation, the KCSE scale can be used in clinical practice to evaluate competence in mobility care based on kinaesthetics and to identify educational needs for nursing staff.